First report of the oomycete Globisporangium splendens causing root rot on custard apple (Annona cherimola Mill.) in Perú - Oviedo-Quirós, Juan José (2023)
Custard apple (Annona cherimola Mill.), originally from the Andean region of Peru and Ecuador, faces a serious threat from root rot, a disease that significantly reduces its yield. In 2015, root damage caused by Dactylonectria macrodidyma was reported in Chile, while Pythium splendens was identified as the root rot culprit in the Annona genus in Australia and Florida. This study aimed to identify the causal agent of custard apple root rot in Peru using PCR. In 2014, twelve ‘Cumbe’ custard apple plants from commercial fields in Ancash and Lima, Peru, displaying symptoms like yellowing leaves and dieback, were examined. The molecular identification was performed through specific rDNA regions (ITS and Cox II) amplification using primers ITS6/ITS4 and FM66/FM58 and revealed the presence of Globisporangium splendens (previously Pythium splendens), which had not previously been recorded as causing this disease in cherimoyas in Peru. Pathogenicity tests confirmed that ‘Cumbe’ custard apple seedlings exhibited consistent symptoms two to three weeks after inoculation, with G. splendens re-isolated from the infected roots. Notably, there were no prior records in Peru of fungal agents causing root rot or quantifying damage in custard apple, marking this as the first report of G. splendens causing the disease in Peru. This research sheds light on a previously unreported threat to custard apple cultivation in the region.